2011
DOI: 10.1080/07418825.2011.585140
|View full text |Cite
|
Sign up to set email alerts
|

Defending the Homeland: Judicial Sentencing Practices for Federal Immigration Offenses

Abstract: In the last decade, immigration prosecutions in federal court have increased 165%, with immigration offenses comprising over 28% of the federal criminal caseload in 2008. Despite this increase, research has yet to fully examine the sentencing outcomes for these offenders. Exploration of sentencing outcomes for immigration offenders is particularly salient due to the racial/ethnic composition of these defendants and the documented history of disparate treatment of minorities at this decision point. To explicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 42 publications
2
31
0
Order By: Relevance
“…For example, examinations of sentencing decision-making demonstrate the importance of criminal history on outcomes (Bushway & Piehl, 2007;Hartley & Tillyer, 2012;Spohn, 2009;Steffensmeier & Demuth, 2000;Steffensmeier, Ulmer, & Kramer, 1998). Recent studies of judge and jury decision-making reveals that juries are more likely to acquit when the defendant does not have a criminal record (Givelber & Farrell, 2008) and that juries may differential weigh the impact of criminal history (Farrell & Givelber, 2010, also see Laudan a Allen (2011) for a more thorough discussion).…”
Section: Stability In Behavior and Criminal Historymentioning
confidence: 94%
“…For example, examinations of sentencing decision-making demonstrate the importance of criminal history on outcomes (Bushway & Piehl, 2007;Hartley & Tillyer, 2012;Spohn, 2009;Steffensmeier & Demuth, 2000;Steffensmeier, Ulmer, & Kramer, 1998). Recent studies of judge and jury decision-making reveals that juries are more likely to acquit when the defendant does not have a criminal record (Givelber & Farrell, 2008) and that juries may differential weigh the impact of criminal history (Farrell & Givelber, 2010, also see Laudan a Allen (2011) for a more thorough discussion).…”
Section: Stability In Behavior and Criminal Historymentioning
confidence: 94%
“…Traditional conceptions of race and ethnicity as static and discrete qualities of offenders need to be challenged in future work, examining important variations that occur within racial and ethnic groups and among more underrepresented groups, such as Asian and Native Americans (Johnson and Betsinger, ). Particular attention needs to be devoted to the changing nature of demography in American society, with a continued focus on the growing Latino population and the potentially important relationship emerging between immigration and punishment (Hartley and Tillyer, ). Recent work on the social contexts of sentencing highlights the significance of court and community characteristics, including the organizational structure of the court and the social, economic, and demographic characteristics of the surrounding community (Ulmer and Johnson, ).…”
Section: Resultsmentioning
confidence: 99%
“…Relatively few studies also consider race of victim effects, except in the context of homicide cases, where there is ample evidence that offenders who target White victims are punished more harshly (Franklin and Fearn, ; Paternoster and Brame, ; Curry, ). One developing area of research examines sentencing outcomes for immigrants in the federal justice system (Wolfe et al ; Hartley and Tillyer, ). For example, Hartley and Tillyer () found that US citizens received significantly shorter terms of imprisonment than non‐US citizens in Southwest border districts.…”
Section: Wave 5 Studies – Recent Research Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The socioeconomic status (SES) of defendants is notoriously difficult to capture, noted scholars calling the existing measures "abysmal" (Zatz, 2000, p. 515). Relatively little work includes measures of citizenship status, though this factor is increasingly being incorporated in recent research on federal sentencing practices, particularly in the context of immigration crimes (Hartley and Tillyer, 2012). Importantly, offenders with similar employment status or educational attainment may have very different life circumstances (Zatz, 2000).…”
Section: Measurement Of Independent Variablesmentioning
confidence: 99%